Proportional Electoral Systems and Number of Parties in Parliament Evidence from Macedonia - Daskalovski Zhidas (Sciendo, 2019)
What is the best electoral system to increase the number of political parties represented in Parliament? This article answers the question using data from all the elections in Macedonia since 2002, and by making simulations of the results according to different electoral systems. In principle, we found that the electoral model that would bring most parties to the Macedonian Parliament is the Droop and Hare used in one electoral district. Moreover, the article answers the question how favourable different electoral systems are to larger/smaller parties. We find that the following is the order of electoral systems from most to least favourable for larger parties: Imperiali highest averages, D’Hondt, Sainte-Laguë, Largest remainders – Imperiali, Danish, Largest remainders – Droop, Largest remainders – Hare.